Synthesis and Characterization of Polypyrrole/TiO2 Nanocomposite using Poly(vinyl alcohol) as a Surfactant - Yousefi Abdolmalki, Aliyeh; Eisazadeh, Hossein; Taghipour, Zahra (Asian Journal of Chemistry, 2011)
In this study nanocomposites of polypyrrole (PPy) and TiO2 were synthesized in aqueous media by polymerization of pyrrole using FeCl3 as an oxidant in the presence of poly(vinyl alcohol) as a surfactant. The PPy/TiO2 nanocomposites were characterized in terms of their particle size, morphology and chemical structure. X-Ray diffraction and fourier transform infrared spectra were used to characterize the structure of the obtained PPy/TiO2 nanocomposites. The morphology of products was characterized by using scanning electron microscope. The results indicate that the morphology and particle size of products are dependent on the surfactant, the type and concentration of metallic oxide.